Fabrication of advanced electrode materials for electrochemical supercapacitor applications - Awad, Mahmoud (My University, 2025)
Electrochemical supercapacitors (ESs) offer a promising energy storage solution due to their high power density, rapid charge–discharge behavior, and long cycle life. This thesis explores the development of advanced electrode materials with innovative synthesis techniques and materials. In this thesis, manganese oxides were synthesized hydrothermally with biocompatible pH modifiers, such as polyethylenimine and meglumine, eliminating the need for inorganic alkalis. In another approach, redox-active organic capping agents—tetrahydroxy-1,4-quinone and 2-hydroxy-1,4-naphthoquinone—were used to control particle size and morphology, forming structured assemblies. Both methods produced electrodes with high mass loading and excellent performance, characterized by minimal activation requirements, high capacitance, low electrical resistance, and high capacitance retention. Another investigation focused on the fabrication of copper oxide–Polypyrrole composite anodes. The combination of these materials produced composites with synergistically enhanced properties. These composites demonstrated improved charge transfer behavior, reduced impedance, and high cycling stability. Asymmetric devices based on these anodes exhibited high capacitance and energy density over a wide voltage window. Moreover, copper ferrite–Polypyrrole composites were also synthesized to improve charge transfer and overall electrode performance. The integration of conductive polymers into the oxide matrix led to significant enhancement in capacitance and cycling behavior. These materials showed enhanced charge storage characteristics and offer potential for applications requiring magnetoelectric or magnetocapacitive effects. Finally, Vanadium pentoxide electrodes were fabricated using high-energy ball milling technique, new dispersants and advanced graphene coated Ni foam current collectors. These electrodes were optimized to achieve low resistance, high charge storage capability, and stability at high charge–discharge rates.
Keywords: Supercapacitors; High mass loading; energy devices; composites; hydrothermal; capping agents; dispersing agents